PELATIHAN AYAT JURNAL PENYESUAIAN PERUSAHAAN DAGANG BAGI SISWA SISWI SMA - Dewi, Syanti (Jurnal Bakti Masyarakat Indonesia, 2024)
Learning about accounting is important, because it is important in daily financial management and needs to be applied from an early age to high school students. In Economics subjects, material about Accounting is not discussed in detail and is only limited to students who choose the social sciences group. Apart from that, students also think that accounting is a dif icult material so they tend not to be interested in this material. Based on these problems, our community service team held training activities with the aim of enriching students' knowledge regarding accounting while changing the perception that accounting is a material that is dif icult to learn. Our team had the opportunity to explain the topic of the trading company accounting cycle, especially the part in preparing adjusting journal entries in November 2023. This training was given to students in classes X (ten), XI (eleven), and XII (twelve) through accounting extracurricular activities provided by Tarsisius High School 1. Training is carried out in face-to-face form, starting with preparing teaching materials, providing theoretical explanations, discussing example questions, then closing with a quiz with prizes which all Tarsisius 1 High School students take part in. Based on the results of the quiz and the good enthusiasm of the Tarsisius 1 High School students can be concluded that the training activities have provided good results and have helped in increasing the students' understanding of the material. ABSTRAK: Pembelajaran mengenai ilmu akuntansi merupakan hal yang penting, karena berkaitan penting dalam pengelolaan keuangan sehari-hari dan perlu diterapkan sejak dini kepada siswa-siswi sekolah menengah. Pada mata Pelajaran Ekonomi, materi tentang akuntansi tidak dibahas secara terperinci dan hanya terbatas bagi siswa-siswi yang memilih rumpun ilmu sosial. Selain itu, siswa-siswi juga menganggap bahwa akuntansi adalah materi yang sulit sehingga mereka cenderung tidak tertarik dengan materi ini. Berdasarkan permasalahan tersebut, Tim pengabdian masyarakat kami, mengadakan kegiatan pelatihan dengan tujuan untuk memperkaya pengetahuan siswa-siswi terkait akuntansi sekaligus mengubah persepsi bahwa akuntansi adalah materi yang sulit dipelajari. Tim kami mendapatkan kesempatan untuk memaparkan topik mengenai siklus akuntansi perusahaan dagang terutama bagian dalam penyusunan ayat jurnal penyesuaian pada bulan November tahun 2023. Pelatihan ini diberikan kepada siswa-siswi kelas X (sepuluh), XI (sebelas), hingga XII (dua belas) melalui kegiatan ekstrakurikuler akuntansi yang disediakan oleh SMA Tarsisius 1. Pelatihan dilaksanakan dalam bentuk tatap muka, dimulai dengan mempersiapkan bahan ajar, melakukan pemaparan teori, membahas contoh soal, lalu ditutup oleh kuis berhadiah yang diikuti seluruh siswa-siswi SMA Tarsisius 1. Berdasarkan kuis serta antusiasme yang baik dari siswa-siswi SMA Tarsisius 1 dapat disimpulkan bahwa kegiatan pelatihan memberikan hasil memuaskan dan telah membantu dalam meningkatkan pemahaman siswa-siswi terkait dengan materi tersebut.